2014
DOI: 10.1002/ar.22896
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Modulus of Cetacean Auditory Ossicles

Abstract: In order to model the hearing capabilities of marine mammals (cetaceans), it is necessary to understand the mechanical properties, such as elastic modulus, of the middle ear bones in these species. Biologically realistic models can be used to investigate the biomechanics of hearing in cetaceans, much of which is currently unknown. In the present study, the elastic moduli of the auditory ossicles (malleus, incus, and stapes) of eight species of cetacean, two baleen whales (mysticete) and six toothed whales (odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…In cetaceans, modelling of sound stimulation of the ears through different anatomical structures of the skull bone, the bony ears and soft tissue (e.g. Tubelli et al, ; Cranford & Krysl, ) has yielded exciting new insights into ear functioning. Outcomes of (or predictions derived from) mathematical modelling, however, may be debated [compare, for example, Lychakov & Rebane, and Krysl et al, ].…”
Section: Functional Morphologymentioning
confidence: 99%
“…In cetaceans, modelling of sound stimulation of the ears through different anatomical structures of the skull bone, the bony ears and soft tissue (e.g. Tubelli et al, ; Cranford & Krysl, ) has yielded exciting new insights into ear functioning. Outcomes of (or predictions derived from) mathematical modelling, however, may be debated [compare, for example, Lychakov & Rebane, and Krysl et al, ].…”
Section: Functional Morphologymentioning
confidence: 99%
“…The sound is then transmitted to the auditory ossicles; malleus, incus and stapes that have been found to be of dense compact bone [3,6]. A high mineralization of bone was found to be of major importance for sound perception as supported by an 86% mineralization of the tympanic bulla with an impressively high Young's modulus [7,8] resulting from mineralization and causing high impedance (a rough approximation of the impedance in case of a wave hitting a material in orthogonal direction can be written by the following equation: Z ¼ ffiffiffiffiffiffiffiffiffi r Á E p ; where Z ¼ impedance, r ¼ density of a material and E ¼ Young's modulus of a material referring to [7]).…”
Section: Introductionmentioning
confidence: 99%
“…As the true Young’s modulus of the bone is uncertain, the range of values that we considered reasonable for the model inputs led to a wider range of possible frequencies and possible modes. The elastic moduli measured by Tubelli et al 2004 [ 10 ] for fin whale ossicles are broad, and may be considered an upper bound, given that bone is porous, and the nanoindentation method they used was by definition applied to the solid framework of the bone. Additionally, the skull used in the experiment had been dried for some time, and studies have shown that Young’s modulus may increase for dried bone [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Citation: Morris M, Krysl P, Hildebrand J, Cranford T (2023) Resonance of the tympanoperiotic complex of fin whales with implications for their low frequency hearing. PLoS ONE 18 (10): e0288119. https://doi.org/10.1371/journal.…”
Section: Open Accessmentioning
confidence: 99%